2017
DOI: 10.4049/jimmunol.1601607
|View full text |Cite
|
Sign up to set email alerts
|

CXCL17 Attenuates Imiquimod-Induced Psoriasis-like Skin Inflammation by Recruiting Myeloid-Derived Suppressor Cells and Regulatory T Cells

Abstract: CXCL17 is expressed in a variety of cancers and promotes tumor progression by recruiting myeloid-derived suppressor cells (MDSCs). MDSCs suppress tumor immunity by attracting regulatory T cells (Tregs) into tumor sites through CCL5. In this study, we examined the role of CXCL17 in skin disorders. CXCL17 mRNA levels in psoriasis skin, but not in lesional skin of atopic dermatitis or cutaneous T cell lymphoma, were significantly higher than those in normal skin. CXCL17 was mainly expressed in the epidermis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 57 publications
4
43
0
2
Order By: Relevance
“…In the present study, treatment with PN gel significantly attenuated the altered expressions of inflammatory mediators in the skin tissue of imiquimod-induced psoriatic mice. This finding is consistent with previously published data [18].…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, treatment with PN gel significantly attenuated the altered expressions of inflammatory mediators in the skin tissue of imiquimod-induced psoriatic mice. This finding is consistent with previously published data [18].…”
Section: Discussionsupporting
confidence: 94%
“…23 A recent report described that CXCL17 attenuates inflammation in a mouse psoriasis model through the recruitment of myeloid derived suppressor cells that can, in turn, recruit regulatory T cells (Tregs). 24 In the present study, we have continued the characterization of a Cxcl17 −/− mouse. We observed abnormalities in the numbers of several T cell populations in both spleen and LNs.…”
Section: Introductionmentioning
confidence: 90%
“…A recent report described that CXCL17 attenuates inflammation in a mouse psoriasis model through the recruitment of myeloid derived suppressor cells that can, in turn, recruit regulatory T cells (Tregs) …”
Section: Introductionmentioning
confidence: 99%
“…In addition, analysis for several other skin diseases was conducted by analyzing UPF1 expression profiles acquired from the GEO database. An independent sample test for Marfan syndrome (GDS2960) showed a significantly increased UPF1 expression in lesions compared with normal tissues, and multiple comparisons for squamous cell carcinoma (GDS2200) and melanoma (GDS1375) showed a high UPF1 expression in squamous cell carcinoma compared with actinic keratosis or normal tissues, and melanoma and benign nevi compared with normal tissues (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). A negative feedback regulatory network that directly acts on UPF1 in response to NMD perturbation has been identified in a previous study which demonstrated that UPF1 itself is a natural substrate of the NMD pathway (6).…”
Section: Discussionmentioning
confidence: 99%